Pemberdayaan Ekonomi Masyarakat melalui Edukasi Pengolahan Minyak Jelantah dari Limbah Menjadi Produk Bernilai Tinggi - Tuti, Meylani; Kurniati, Yeni; Paludi, Salman (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The problem of used cooking oil waste in households is often ignored, even though it has the potential for negative impacts on the environment if not managed properly. This study aims to empower the community in Ciherang Housing, Bogor, through education on processing used cooking oil into high-value products such as soap and aromatherapy candles. The method used in community service is Participatory Action Research (PAR), where the community is actively involved in every stage of the activity, from identifying needs, and training, to evaluating results. This program consists of several stages, namely socialization of the dangers of used cooking oil for the environment, training on processing used cooking oil into processed products, and production assistance for program sustainability. The results of this activity showed that participants experienced increased knowledge about the impact of used cooking oil on the environment and skills in processing used cooking oil into economical products. Around 80% of participants succeeded in producing soap and candles that were suitable for use, and 40% of them showed interest in marketing their processed products. In addition, the formation of small production groups among participants also indicates the potential for sustainability of this program. This education and training not only reduces environmental pollution but also opens up additional income opportunities for the community. It can be concluded that the empowerment program through education on used cooking oil processing is effective in increasing environmental awareness and community economic skills. This program is expected to be a model that can be applied in other areas as a solution for sustainable environmental-based economic empowerment.